Misaligned Incentives and Mortgage Lending in Asia - GREEN, Richard (Institutional Knowledge at Singapore Management University, 2009)
This paper provides a conceptual basis for the price discovery potential for tradable market instruments and specifically the development of mortgage securitization in Asia and the potential dangers of such markets. Nonetheless we argue for the potential importance of securitization in Asia because of its possible role in increasing transparency of the financial sector of Asian economies. We put forth a model explaining how misaligned incentives can lead to bank generated real estate crashes and macroeconomic instability, with or without securitization under certain circumstances. We examine the banking sector’s performance in Asia compared to securitized real estate returns, to provide evidence on the contribution of misaligned incentives in the past. We discuss how the addition of liquid MBS could help to inoculate markets from the shocks arising from bank-financed mortgage lending. We conclude with a brief discussion of current MBS markets in Asia.